Psychiatric comorbidities and use of psychotropic medications in people with autism spectrum disorder in the United States. Issue 12 (30th September 2017) - Houghton, Richard; Ong, Rose C.; Bolognani, Federico
Abstract : This study investigated psychotropic medication usage in two large, cohorts of people with autism spectrum disorder (ASD) throughout the calendar year 2014. The cohorts referred to individuals with commercial (employer‐sponsored) and Medicaid insurance in the United States. We aimed to understand prescribing patterns of such medications across a wide age‐range and in the presence/absence of other clinical and non‐clinical characteristics, including psychiatric comorbidities. We described the prevalence and length of prescriptions by age, psychiatric comorbidity and overall. We also fitted multivariable logistic regression models to describe the relationship between treatments and subject characteristics simultaneously. Eighty percent of the identified population was male, although gender did not impact the odds of receiving medication. Medication use was strongly associated with age, increasing most rapidly before adulthood; generally plateauing thereafter. All psychiatric comorbidities studied also individually increased the chances of medication use, with epilepsy and ADHD having the highest associations in both the commercial (OR > 7) and Medicaid (OR around 12) cohorts. Those in non‐capitated insurance plans, in foster care and white individuals also had increased odds of prescriptions. Overall, slightly more Medicaid enrollees received any psychotropic treatment (commercial: 64%, Medicaid: 69%). Nonetheless in both cohorts, a large proportion of individuals received treatment even without a diagnosis of any other psychiatric comorbidity (commercial: 31%, Medicaid: 33%). In summary, this report sheds new light on the latest patterns of psychiatric comorbidity profile and psycho‐pharmacological treatment patterns in ASD Autism Res 2017, 10: 2037–2047 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: this study identified a large number of children and adults in the US with autism spectrum disorder (autism) from employer‐sponsored and government funded (Medicaid) health insurance data. Psychotropic medications were used by over two thirds of people, and four in ten people received two medications at the same time. The chances of receiving medication increased for individuals with other psychiatric conditions (e.g., ADHD), and also increased with age.